Analisa Faktor Internal dan Perencanaan MSDM pada Industri Minyak Kayu Putih dengan Memanfaatkan IoT - Arief Pribadi; Tantri Yanuar Rahmat Syah; Hamdi, Edi; Sunaryanto, Ketut (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
The eucalyptus oil industry is one of the agroindustrial sectors that has strategic potential in Indonesia. However, the industry faces challenges in managing internal factors and human resource management (HRD) planning, especially related to production efficiency, limited skilled labor, and the need for consistent quality control. This study aims to analyze the internal factors that affect the performance of the eucalyptus oil industry and formulate MSDM planning by utilizing Internet of Things (IoT) technology. The research method used is a descriptive qualitative approach supported by quantitative data, through interviews, field observations, and literature studies related to the implementation of IoT in the agro-industrial sector. The results of the analysis show that the use of IoT can increase the effectiveness of monitoring production processes, quality control, and transparency of operational data. In addition, IoT integration requires adaptive HR planning, including improving the digital competence of the workforce, developing technology-based training systems, and restructuring the division of tasks to be more efficient. Thus, the combination of internal factor optimization and IoT-based MSDM planning is able to strengthen the competitiveness of the eucalyptus oil industry in a sustainable manner. The recommendations in this study are that the IoT dashboard will integrate production, inventory, and distribution data to support data-driven strategic decision-making. Using IoT data as an objective indicator in assessing employee performance.